Formation of complex organic molecules in astrophysical environments: Sugars and derivatives. Issue Volume 15:Issue S350(2019) (April 2019) - Nuevo, Michel; Cooper, George; Saunders, John M.; Buffo, Christina E.; Sandford, Scott A.
Abstract: Carbonaceous meteorites contain a large variety of complex organic molecules, including amino acids, nucleobases, sugar derivatives, amphiphiles, and other compounds of astrobiological interest. Photoprocessing of ices condensed on cold grains with ultraviolet (UV) photons was proposed as an efficient way to form such complex organics in astrophysical environments. This hypothesis was confirmed by laboratory experiments simulating photo-irradiation of ices containing H2 O, CH3 OH, CO, CO2, CH4, H2 CO, NH3, HCN, etc., condensed on cold (~10–80 K) substrates. These experiments resulted in the formation of amino acids, nucleobases, sugar derivatives, amphiphilic compounds, and other organics comparable to those identified in carbonaceous meteorites. This work presents results for the formation of sugars, sugar alcohols, sugar acids, and their deoxy variants from the UV irradiation of ices containing H2 O and CH3 OH in relative proportions 2:1, and their comparison with meteoritic data. The formation mechanisms of these compounds and the astrobiological implications are also discussed.